ANALISIS HUBUNGAN TINGKAT BUNGA, INFLASI DAN PERTUMBUHAN JUMLAH UANG BEREDAR DI INDONESIA TAHUN 1982-2011 (PENDEKATAN ERROR CORRECTION MODEL) - Kristiyanto, Sony (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2012)
Until recent days, the problem as if the interest rate will never be finished to be discussed. The interest rate is no longer seen as a problem or a mere economic phenomenon, but it has become a social phenomenon. In analyzing a country's economy, one of the variables commonly used is the interest rate. In a economics theory, interest rates are closely related to other economic variables is the variable growth of money supply and inflation. This paper will discuss further on the matter. By using Error Correction Model (ECM) approach, and took the time span between 1982 to 2011, this paper tries to review further the relationship of the three economic variables above. ECM is used because itis able to explain the relationship between the variables studied both shortterm and also long term relationship. Furthermore,by using the Koyk’s transformation, can be calculated lag time required for the independent variable can affect the dependent variable. This study came to the conclusion that the inflation variable, lag of inflation and lag of growth in the money supply affect the interest rate changes during the observation period between 1983 to 2012, while the growth in the money supply has no effect.